(untitled) (Khairulummah, 2021)
The graph of development of Islamic Banking system is increasing day by day. It deals only those transaction which are not conflict with Shari’ah. Therefor the procedure of transaction of Islamic Banking is completely different from the conventional Banking system. Murābaha (Cost plus sale) or Murābaha li al-Āamir be al-Shēraá. (Cost plus sale for the purchase orderer) is a well-known financing mood. In this mood of financing, the Islamic bank bound to buy the required goods to the orderer and to sells him at higher price than the purchase price. Islamic Banks occasionally appoints an agent to buy the goods. Sometime the Islamic Banks appoints the purchase ordere himself as an agent. In this case, the contract of Murabaha and the contract of agency should not be related to each other. When the purchase orderer buys the goods as an agent, he will inform the Bank of his purchase, and the possession of the agent will be considered as the possession of the Bank. In this way, both contracts Murābaha and Wakālah are not related to each other. After this, the Bank will offer to sell him (purchase orderer) the goods and then he will accept the offer.